One-step degradation of cellulose to 5-hydroxymethylfurfural in ionic liquid under mild conditions. (6th March 2015) - Zhou, Lilong; He, Yiming; Ma, Zhanwei; Liang, Runjuan; Wu, Tinghua; Wu, Ying
Highlights: Different metal chlorides (CrCl3, CuCl2, SnCl4, WCl6 ) were used to convert cellulose to HMF. Cellulose was directly converted to HMF in 63% yield by CrCl3 in [BMIM]Cl at 120 °C. This catalysis system can be reused for many times. The mechanism of this reaction was studied. Abstract: One-step conversion of cellulose to HMF (5-hydroxymethylfurfural) has been achieved by using metal chlorides (CrCl3, CuCl2, SnCl4, WCl6 ) in [BMIM]Cl. The effects of temperature, reaction time, amount of catalysts, and the purity of [BMIM]Cl on the performance have been studied and discussed in detail. More than 63% yield of HMF and 80% yield of TRS (total reducing sugar) were obtained in [BMIM]Cl with CrCl3 at 120 °C under atmospheric pressure. Filter paper and cotton were also used as a source for cellulose degradation to HMF, but only a moderate yield of HMF was obtained (40% for filter paper and 12% for cotton). The reutilization of this system was examined and the reaction mechanism was also discussed.